Improving diagnostic accuracy in the transport of infants with suspected duct‐dependent congenital heart disease. (6th October 2013) - Gupta, Neelam; Kamlin, C Omar; Cheung, Michael; Stewart, Michael; Patel, Neil
<x xml:space="preserve">Abstract</x> Aim To identify factors that distinguish duct‐dependent congenital heart disease (DDCHD) from non‐DDCHD in newborn infants. Method A retrospective, cohort study. The Newborn Emergency Transport Service, Victoria (NETS) is a retrieval service for all inter‐hospital neonatal transfers, and the Royal Children's Hospital, Melbourne (RCH) is a paediatric cardiac referral centre for the state of Victoria, Australia. All infants ≤10 days and ≥34 weeks gestation with suspected CHD and/or persistent pulmonary hypertension of the newborn (PPHN), transferred by NETS from non‐tertiary neonatal units to RCH, over a 4‐year period. Results Of 142 eligible infants, 81 had DDCHD and 61 had non‐DDCHD, of whom 51 had PPHN. Diagnostic accuracy of DDCHD by the NETS team was 77%. Presence of a heart murmur, abnormal pulses, upper and lower limb blood pressure (BP) difference >10 mmHg, cardiomegaly, initial SpO2 of <92%, PaO2 <50 mmHg, and pre‐post ductal SpO2 difference >10% were significantly associated with DDHCD on univariate analysis. No single clinical finding was significantly associated with DDCHD on multivariate analysis. Labile SpO2, abnormal lung parenchyma, mean BP <40 mmHg, pH <7.25, lactate >5 and FiO2 >0.5 were significantly associated with non‐DDCHD, but at multivariate analysis only labile SpO2 and mean BP <40 mmHg were associated with non‐DDCHD. Conclusions Clinical diagnosis of DDCHD outside of a cardiac centre is challenging. No single factor predicts DDCHD. Combined interpretation of clinical, physiological and x‐ray findings may assist.